POTENTIALLY OF PURPLE LEAVES TO INCREASE OSTEOBLASTAT ALVEOLAR BONE RAT INDUCED PORPHYROMONAS GINGIVALIS - Dyasti, Pramita Wahyu; Kurniawati, Atik; Pujiastuti, Peni (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: Periodontal disease are common dental and oral health problems in the community. Porphyromonas gingivalis (Pg) is one of the main causes of the periodontal disease. The alveolar bone resorption could be as severity indicator of the disease, so that need a material that can help a process of bone remineralization. Osteoblasts are bone-forming cells that are responsible for the mineralization of the bone matrix. Purple leaf is one of the thirteen commodities developed by DitjenPOM as a superior medicinal plant. Purpose: To determine the effect of 2,5%, 5% and 10% purple leaf extract (EDU) of osteoblasts cells in wistar rats induced by Pg. Method: Thirty male wistar rats divided into 5 groups, namely N (without treatment), K (Pg), P (Pg+EDU 2,5%), P2 (Pg+ EDU 5%), P3 (Pg+EDU 10%). EDU administration once a day for 7 days. The mice were decaputated on the 7 th day and the left mandible was taken to make preparations followed by HE staining, observation and calculation of the number of osteoblast cells in 3 different fields. The results of the observations (data) were added up, averaged and analyzed by One Way ANOVA. Result: The group induced by Pg and EDU had a higher average number of osteoblasts than the K and N group. Conclusion: Purple leaf extract (EDU) can increase osteoblasts cells in the alveolar bone of male wistar rats induced by Pg with the highest number of osteoblasts in the 10% concentration.